The neuronal and astrocytic protein SLC38A10 transports glutamine, glutamate, and aspartate, suggesting a role in neurotransmission. Issue 6 (26th April 2017) - Hellsten, Sofie V.; Hägglund, Maria G.; Eriksson, Mikaela M.; Fredriksson, Robert
Abstract : In brain cells, glutamine transporters are vital to monitor and control the levels of glutamate and GABA. There are 11 members of the SLC38 family of amino acid transporters of which eight have been functionally characterized. Here, we report the first histological and functional characterization of the previously orphan member, SLC38A10. We used pairwise global sequence alignments to determine the sequence identity between the SLC38 family members. SLC38A10 was found to share 20–25% transmembrane sequence identity with several family members, and was predicted to have 11 transmembrane helices. SLC38A10 immunostaining was abundant in mouse brain using a custom‐made anti‐SLC38A10 antibody and colocalization of SLC38A10 immunoreactivity with markers for neurons and astrocytes was detected. Using Xenopus laevis oocytes overexpressing SLC38A10, we show that SLC38A10 mediates bidirectional transport ofl ‐glutamine, l ‐alanine, l ‐glutamate, andd ‐aspartate, and efflux ofl ‐serine. This profile mostly resembles system A members of the SLC38 family. In conclusion, the bidirectional transport of glutamine, glutamate, and aspartate by SLC38A10, and the immunostaining detected in neurons and astrocytes, suggest that SLC38A10 plays a role in pathways involved in neurotransmission. Abstract : SLC38A10 is a member of the SLC38 family of amino acid transporters. In the mouse brain, SLC38A10 immunostaining was detected throughout, in both neurons and astrocytes using immunohistochemistry. The substrate profile was determined using radiolabeled transport assays on Xenopus laevis oocytes overexpressing SLC38A10. SLC38A10 mediates bidirectional transport ofl ‐glutamine, l ‐glutamate, l ‐alanine, andd ‐aspartate, and efflux ofl ‐serine. This suggests that SLC38A10 plays a role in neurotransmission.